2014
DOI: 10.1038/ngeo2277
|View full text |Cite|
|
Sign up to set email alerts
|

Robust Arctic sea-ice influence on the frequent Eurasian cold winters in past decades

Abstract: Over the past decade, severe winters occurred frequently in mid-latitude Eurasia 1,2 , despite increasing global-and annual-mean surface air temperatures 3 . Observations suggest that these cold Eurasian winters could have been instigated by Arctic sea-ice decline 2,4 , through excitation of circulation anomalies similar to the Arctic Oscillation 5 . In climate simulations, however, a robust atmospheric response to sea-ice decline has not been found, perhaps owing to energetic internal fluctuations in the atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
635
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 691 publications
(703 citation statements)
references
References 28 publications
65
635
2
1
Order By: Relevance
“…The decreases or weakening of convection over the JPCZ were accounted for by the weakening of large-scale, low-level northwesterly winds associated with the winter monsoon. Mori et al (2014) concluded that cold winters driven by Arctic sea ice unlikely occur in the future climate, which is consistent with our results, although decreases in the ice may cause severe winter over central Eurasia in past decades.…”
Section: Summary and Concluding Remarkssupporting
confidence: 82%
“…The decreases or weakening of convection over the JPCZ were accounted for by the weakening of large-scale, low-level northwesterly winds associated with the winter monsoon. Mori et al (2014) concluded that cold winters driven by Arctic sea ice unlikely occur in the future climate, which is consistent with our results, although decreases in the ice may cause severe winter over central Eurasia in past decades.…”
Section: Summary and Concluding Remarkssupporting
confidence: 82%
“…Meanwhile, SIC was assimilated at 1-day intervals following Lindsay and Zhang (2006) and Stark et al (2008). These assimilations were conducted over the period 1975-2011 with eight ensemble members produced by perturbing the sea surface temperature based on observational errors.…”
Section: Experimental Designmentioning
confidence: 99%
“…Although the exact cause is still being debated (e.g., Barnes and Screen, 2015), Mori et al (2014) have shown, using ensemble experiments with an atmospheric general circulation model, that the more frequent cold winters at midlatitudes can be partly explained by the sea ice decrease in the Barents and Kara Seas. Therefore, further investigation of the mechanisms driving Arctic sea ice variability is of great importance for more accurate projections of climate change, not only in the Arctic but also for the midlatitudes.…”
Section: Introductionmentioning
confidence: 99%
“…To do this, we fi rst establish a reference EOF loading pattern based on the JRA-55 dataset. Region selected is 0°E−150°E, 40°N−90°N, slightly different from the defi nition used in Mori et al (2014). Next, for each ensemble run of both HPB and HPB-NAT experiments, we perform the same EOF analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Mori et al (2014) showed through 100-member ensemble simulation of an atmospheric general circulation model (AGCM) that the second empirical orthogonal function (EOF) pattern reflecting such Arctic warming and mid-latitude cooling is robust and is approximately independent of the Arctic Oscillation (AO) signature. The pattern is named Warm Arctic/Cold Eurasian (WACE) and will be used to designate the pattern throughout this study.…”
Section: Introductionmentioning
confidence: 99%